Previous History of American Tegumentary Leishmaniasis Alters Susceptibility and Immune Response Against Schistosoma mansoni Infection in Humans - Miranda, Guilherme Silva; Resende, Samira Diniz; Cardoso, Diogo Tavares; Camelo, Genil Mororó Araújo; Silva, Jeferson Kelvin Alves Oliveira; Castro, Vanessa Normandio de; Geiger, Stefan Michael; Carneiro, Mariângela; Negrão-Corrêa, Deborah (Frontiers in Immunology, 2021)
Schistosomiasis and Leishmaniasis are chronic parasitic diseases with high prevalence in some tropical regions and, due to their wide distribution, a risk of co-infections is present in some areas. Nevertheless, the impact of this interaction on human populations is still poorly understood. Thus, the current study evaluated the effect of previous American Tegumentary Leishmaniasis (ATL) on the susceptibility and immune response to Schistosoma mansoni infection in residents from a rural community in Northern of Minas Gerais state, Brazil, an area endemic for both parasitic infections. The participants answered a socioeconomic questionnaire and provided stool and blood samples for parasitological and immunological evaluations. Stool samples were examined by a combination of parasitological techniques to identify helminth infections, especially S. mansoni eggs. Blood samples were used for hemograms and to measure the serum levels of cytokines and chemokines. Reports on previous ATL were obtained through interviews, clinical evaluation forms, and medical records. S. mansoni infection was the most prevalent parasitic infection in the study population (46%), and the majority of the infected individuals had a very low parasite burden. In the same population, 93 individuals (36.2%) reported previous ATL, and the prevalence of S. mansoni infection among these individuals was significantly higher than among individuals with no ATL history. A multiple logistic regression model revealed that S. mansoni infection was positively associated with higher levels of CCL3 and CCL17, and a higher frequency of IL-17 responders. Moreover, this model demonstrated that individuals with an ATL history had a 2-fold higher probability to be infected with S. mansoni (OR = 2.0; 95% CI 1.04-3.68). Among S. mansoni-infected individuals, the logistic regression demonstrated that a previous ATL history was negatively associated with the frequency of IL-17 responders and CXCL10 higher responders, but positively associated with higher IL-27 responders. Altogether, our data suggest that previous ATL may alter the susceptibility and the immune response in S. mansoni-infected individuals, which may likely affect the outcome of schistosomiasis and the severity of the disease in humans.